Assessment of inflammatory biomarkers in pulmonary arteries of chagasic and non-chagasic heart transplant recipients - Vinícius de Paula da Silva, Marcus; Vieira Alves, Ildernandes; Rodrigues Pereira Alves, Antonielle; Soares Lemos, Virginia; Assis Lopes do Carmo, Gabriel; Morato de Castilho, Fábio o; Léo Gelape, Cláudio (Brazilian Journal of Transplantation, 2024)
Heart transplantation (TxC) is a therapeutic option considered in patients with advanced heart failure (IC) refractory to optimized treatment, according to national and international guidelines. IC is a progressive disease that affects millions of people. Patients with advanced IC often develop pulmonary arterial hypertension (HAP). HAP is defined as a condition in which the mean pulmonary artery pressure is greater than 20 mmhg. In relation to HAP, it is recognized that inflammation is an important aspect in its development. Objective: In this context, the objective of this work was to evaluate the relationship between the inflammatory process and the development of HAP in patients undergoing TxC. Methods: The levels of interleukins IL-6, IL-1β and TNF-α were obtained by ELISA, associated with CD68 and CD66b neutrophil counts using the immunofluorescence technique, in fragments of the pulmonary arteries of patients with chagasic cardiomyopathy or who had not undergone TxC. Results: The study revealed that there is no statistically significant difference (p ≥ 0.05) between chagasic recipients and non-chagasic recipients with regard to clinical, echocardiographic, manometric variables and inflammatory markers. Conclusion: These data suggest the presence of a pro-inflammatory profile in TxC, independent of measured pulmonary artery pressure levels